Tissue culture, its morphological and biochemical integrity and antioxidant profiling on Cucumis sativus L. cv. MTI2 - Ku Hasan, Tg Azia Farahin (2015)
Cucumber is one of the high-nutritional vegetable and is one of the most important crops worldwide. It is rich in vitamin B, vitamin C, proteins, minerals, amino acids and many other constituents. It is beneficial for people to consume cucumber which offer health benefits and aid in disease prevention such as cancer. Cucumber variety MTi2 is one of the famous cucumber variety in Malaysia that consumed by local people. Therefore it is important to maintain the good supply of this favorable variety and to conserve the species to ensure its continuance in the future. Also, the outbreak of viral disease prompts us to look alternative method to safe keep viable stock plant. Besides, the conventional means of propagation commonly yield non uniform plants that may reduce the crop quality. This might be a huge problem for large scale multiplication industries and for conservation purpose of the species. As an alternative, in vitro regeneration was carry out to optimize the protocol in obtaining uniform plantlet through culturing shoot apical meristem (SAM) of cucumber. Nevertheless, in vitro regeneration is also associated with somaclonal variation that may result of producing non uniform plantlet. Therefore the SAM culture was optimized in this study to generate identical plantlet. The effect of plant growth regulators (PGR) in in vitro regeneration was also studied through application of 10 treatments of full strength MS media supplemented with different concentration and combination of PGR, with MS basal media served as control treatment. The result showed that meristem tissue of cucumber can be regenerated into whole plant through in vitro micropropagation. The combination treatment of 0.01 mgL-1 IAA and 0.1 mgL-1 KIN produced highest percentage survival of plantlets which was 88%. Comparative study was done in term of morphology, anatomy, biochemical and antioxidant profiling between cucumber plant and cucumber plantlet. The finding showed that the plantlet possess similar characteristics as the cucumber plant in term of morphology, anatomy, total protein content, total phenolic content and total flavonoid content. In conclusion, identical plantlet can be produced through in vitro regeneration of SAM of cucumber, thus this technique can be implemented for conservation and for large-scale multiplication purpose. This study had also identify and compared the antioxidant activity between seed, young fruit and matured fruit of cucumber. Antioxidant play vital roles in neutralize the effects of free radicals where free radicals are molecules that can damage the cellular components in human body. Phenolic and flavonoid are examples of antioxidant properties measured in this study. The finding showed that the seed of cucumber possess considerate amount of antioxidant properties which is 0.2 mg/ml flavonoid content and 0.02 mg/ml phenolic content. Therefore, the seed of cucumber can be utilized as a dietary source of natural antioxidant.